Comparison of intraoperative imprints cytology with frozen section for lymph node metastasis in patients with head and neck squamous cell carcinoma. Issue 2 (25th September 2020) - Neduvanchery, Saheer; Gochhait, Debasis; Srinivas, Bheemanathi Hanuman; Harichandrakumar, K T; Subramanian, Pradeep; Shukkur, Naveeth; Keerthana, K; Penumadu, Prasanth
Abstract: Background: Intraoperative evaluation of lymph nodal metastasis in head and neck squamous cell carcinoma (HNSCC) assumes importance and avoids over‐treatment in clinically node negative (N0) neck. Frozen section (FZ) is the commonly employed technique, but it requires significant investment in resources, time, and personnel. Intraoperative imprint cytology (IC) is a rapid, reliable, and inexpensive alternative. We conducted a prospective study to assess the diagnostic accuracy of intraoperative IC and FZ for lymph node metastasis in HNSCC. Methods: All patients presenting with HNSCC with clinically N0 neck undergoing surgery were included in the study, and intraoperative assessment of clinically suspicious nodes was done using IC and FZ and was reviewed by two independent pathologists. The sensitivity, specificity, and accuracy of IC and FZ were calculated with reference to the final histopathology report. The time duration for reporting was calculated. Results: Thirty‐four patients with clinically N0 neck were included in the study, and 85 slides were examined. The sensitivity, specificity, and accuracy of FZ were 100%, 98.6%, and 98.9%, respectively, whereas for IC, it was 85.7%, 95.8%, and 94.1%, respectively. The mean time duration for reporting for FZ and IC was 41.18 ± 3.62 and 18.12 ± 2.01 minutes, respectively. Conclusion: IC provides a cheaper, accurate, and rapid alternative for FZ for intraoperative assessment of neck nodes in HNSCC, and it assumes importance in resource‐driven countries like India.